Blood biochemistry reference values for wild juvenile loggerhead sea turtles (Caretta caretta) from Madeira archipelago - Delgado, Cláudia (2011)
Standard biochemical parameters were determined in wild juvenile loggerhead sea turtles Caretta caretta living offshore Madeira Island, northeast Atlantic. We analyzed the influence of age, sex, sea surface temperature, and body condition index on biochemical parameters including uric acid, total bilirubin, total cholesterol, creatinine kinase (CK), glucose, total protein, urea nitrogen, lactate dehydrogenase, aspartate aminotranspherase (AST), gamma-glutamyl transferase (GGT), albumin, alkaline phosphatase (ALP), sodium (NA), potassium (K), chloride, calcium, phosphorus, and magnesium. Significant positive correlations were found between turtle body size and total cholesterol, total protein, and albumin. Total protein and the enzymes AST and CK were lower than reported levels in adults. Calcium levels were lower than those reported in adult or captive turtles, but similar to wild juveniles from Australian waters, and were interpreted as normal for this age category. These data may be useful to evaluate the health status of stranded or injured animals and to improve veterinary care at rehabilitation centers.